Ciência e política: memória das Memórias do Instituto Oswaldo Cruz (1964-2018) - Amorim Neto, Miguel Romeu (2019)
This is an exploratory and quantitative research, which to achieve the proposed objective were used methods that fit the statistical methodologies of data collection and analysis. The objective of the study was the phenomenon of obsolescence, in particular, as the age of the biomedicine literature has changed over 54 years of scientific activity, based on the analysis of the journal Memories of the Oswaldo Cruz Institute. One hypothesis that was tested was the possibility that the themes (subjects) of the articles influence the half-life of the publication, which was not confirmed. A characterization of the historical context was performed, analyzing the scientific and technological policies implemented during the same period, and it was found that there is an influence of these on the obsolescence phenomenon. The results also point out that the magazine's obsolescence follows international trends.